2020
DOI: 10.1186/s12879-020-05495-5
|View full text |Cite
|
Sign up to set email alerts
|

Continuous thrombocytopenia after SARS-CoV-2 nucleic acid negative in a non-severe COVID-19 patient for several months

Abstract: Background Thrombocytopenia was common in the coronavirus disease (Covid-19) patients during the infection, especially in severe COVID-19 patients, but was less in the non-severe Covid-19 patients. However, the platelet count would be restored after antivirus treatment. In this paper, we report continuous thrombocytopenia in a non-severe Covid-19 case after a negative nucleic acid test for Covid-19. Case presentation A non-severe COVID-19 patient had the platelet continuous decrease for several months after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…One of the therapeutic approaches that is considered for COVID-19 patients with thrombocytopenia and life-threatening hemorrhage is platelet transfusions, but serious caution should be measured as unnecessary transfusions may increase the risk of thrombotic events in patients with coagulopathy or ITP [10] . Wu et al indicated that platelet transfusion together with 10 mg dexamethasone could remarkably increase PLT count by 30 × 10 9 /L and ameliorate the bleeding in COVID-19 patients [146] . Lévesque et al also treated a COVID-19 patient with ITP and bleeding event with IVIG (1 g/Kg), dexamethasone (40 mg/day), and several PLT and RBC transfusions [147] .…”
Section: Thrombocytopenia-related Treatment In Covid-19mentioning
confidence: 99%
“…One of the therapeutic approaches that is considered for COVID-19 patients with thrombocytopenia and life-threatening hemorrhage is platelet transfusions, but serious caution should be measured as unnecessary transfusions may increase the risk of thrombotic events in patients with coagulopathy or ITP [10] . Wu et al indicated that platelet transfusion together with 10 mg dexamethasone could remarkably increase PLT count by 30 × 10 9 /L and ameliorate the bleeding in COVID-19 patients [146] . Lévesque et al also treated a COVID-19 patient with ITP and bleeding event with IVIG (1 g/Kg), dexamethasone (40 mg/day), and several PLT and RBC transfusions [147] .…”
Section: Thrombocytopenia-related Treatment In Covid-19mentioning
confidence: 99%
“…Heparin administration restored the damaged endothelial cells, protected endothelial cells from leukocyte adhesion, and dismantled NETs, which prevented further cytokine release and thrombus formation [ 18 , 19 ]; and eventually the patient’s D-dimer, ferritin, and sIL-2R levels normalized. We hypothesize that heparin rather than steroid [ 20 ] administration, is essential to treat DVT and PE affected by dexamethasone administration.…”
Section: Discussionmentioning
confidence: 99%
“…This observation heightens concerns over the potential long-term clinical consequences of COVID-19 [11,12] Among the various clinical and laboratory manifestations of the disease described throughout the COVID-19 pandemic, investigations of the hematological profile have proven important in the risk assessment of severe cases of COVID-19. Patients with an unfavorable disease evolution have hypercoagulable states and changes in platelet, leucocyte, and erythrocyte counts, indicating a poor prognosis; these parameters should be observed carefully [6,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies indicate that the hematological profile may remain altered during long COVID, with thrombotic events and leukocyte count imbalances observed [13][14][15]. Furthermore, while long COVID symptoms vary, abnormalities in hematological markers, particularly clotting parameters, related to COVID-19 infection are believed to play a role in the pathogenesis of long COVID symptoms [16].…”
Section: Introductionmentioning
confidence: 99%